x → 1 lim x − 1 x n − 1 Compute the limit above for n = 0 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Yeah, I also thought of it. :-)
The above numerator can be factored into x n − 1 = ( x − 1 ) ( x n − 1 + x n − 2 + . . . + x + 1 ) , and the x − 1 factor cancels with the denominator. The latter nonlinear factor contains n terms which the limit equals:
l i m x → 1 Σ k = 0 n − 1 x k = Σ k = 0 n − 1 1 = n .
Let S = 1 + x + x 2 + x 3 + ⋯ + x n So x S = x + x 2 + x 3 + ⋯ + x n + x n + 1 x S − S = x n + 1 − 1 S = x − 1 x n + 1 − 1 When x → 1 , the formula's (not S ) value is 1 + 1 + 1 2 + 1 3 + ⋯ + 1 n − 1 = 1 × n = n . Choose the third.
I don't know why I can't put x → 1 directly below lim .
Log in to reply
Problem Loading...
Note Loading...
Set Loading...
If we replace x = 1 in the given expression, we will get 0 0 which is an indeterminate form so we need to apply L’Hopital’s Rule
ApplyingL’Hopita’s Rule :
x → 1 lim ∂ x ∂ ( x − 1 ) ∂ x ∂ ( x n − 1 ) = x → 1 lim 1 n x n − 1 = n